A comparative study of four physical education curricula on the developmental behavior of Chinese preschool children aged 4 to 6 years and its correlation with balance ability - Minjie Qiao; Minjie Qiao; Laite Yu; Laite Yu; Jingyu Shi; Xiaoting Wang; Xiaoting Wang; Ruiyuan Li; Ruiyuan Li; Zicheng Wan; Zicheng Wan; Dongsheng Lu; et al. (Frontiers in Public Health)
Early childhood development is important for the future developmental behavior, physical fitness, and social adaptation. The content of the physical education curriculum in kindergarten is crucial for the growth of preschool children. The aim of this study was to explore the effects of 12-week of 4 different physical education curriculum interventions on developmental behavior and balance ability, and the correlation between these two factors in preschool children. 94 preschool children aged 4–6 years were stratified and randomly assigned to tennis group (TG), football group (FG), sensory integration group (SIG), and control group (CG). All interventions resulted in greater improvements in all developmental behavior indicators and balance ability after intervention compared to baseline. The SIG showed greater improvements in total development quotient (DQ), gross motor DQ, fine motor DQ, and balance ability than the other three groups after intervention. No significant difference in balance ability between FG and SIG was found. There was a positive and significant correlation between adaptability DQ, social behavior DQ, and balance ability after SIG intervention. The SIG training could correlate children’s balance ability with their social behavior and adaptability. The sensory integration curriculum might be the optimal curriculum to promote the efficient improvement of preschool children’s developmental behavior and motor competence.